2022
DOI: 10.3390/ma16010097
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural and Magnetic Properties of Cobalt-Doped GaN Nanowires on Si by Atmospheric Pressure Chemical Vapor Deposition

Abstract: GaN nanowires (NWs) grown on silicon via atmospheric pressure chemical vapor deposition were doped with Cobalt (Co) by ion implantation, with a high dose concentration of 4 × 1016 cm−2, corresponding to an average atomic percentage of ~3.85%, and annealed after the implantation. Co-doped GaN showed optimum structural properties when annealed at 700 °C for 6 min in NH3 ambience. From scanning electron microscopy, X-ray diffraction, high resolution transmission electron microscope, and energy dispersive X-ray sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Since an experimental reports of T C reaching 200K in (Ga,Mn)As by patterning a heavily Mn-doped (Ga,Mn)As films into NWs [23], this success has inspired researchers to be interested in DMS NWs that takes advantage of the quantum size effect and surface effect of the NW. At the experimental level, the room temperature DMS NWs were developed using Mn-doped GaN NWs [24], Co-doped GaN NWs [25,26], Co-doped ZnO NWs [27], and (Cu,N)-codoped In 2 O 3 NWs [28]. Theoretically, Zhang et al suggested that the magnetic moment and the ferromagnetic states in (Ga,Mn)As NWs can be effectively regulated by the surface dangling bonds [29].…”
Section: Introductionmentioning
confidence: 99%
“…Since an experimental reports of T C reaching 200K in (Ga,Mn)As by patterning a heavily Mn-doped (Ga,Mn)As films into NWs [23], this success has inspired researchers to be interested in DMS NWs that takes advantage of the quantum size effect and surface effect of the NW. At the experimental level, the room temperature DMS NWs were developed using Mn-doped GaN NWs [24], Co-doped GaN NWs [25,26], Co-doped ZnO NWs [27], and (Cu,N)-codoped In 2 O 3 NWs [28]. Theoretically, Zhang et al suggested that the magnetic moment and the ferromagnetic states in (Ga,Mn)As NWs can be effectively regulated by the surface dangling bonds [29].…”
Section: Introductionmentioning
confidence: 99%